(3QaY GdNaG Yf PGJ GdTaG aj SjQI GdeUWais - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s ((3GdSjO CMeO Hf GdSjO eMeO UGdM Hf SjO NVQ GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef HNdjaJg GdCcHQ` fHjg Edi YGeI GdCShO hGdCMeQ s
(3BNQgG (B:s
(3hCMeOg Ydi Cf ef Ydj HEceGd gPG GdTQM GdeMQQ Hd GdcHQjJ GdCMeQ JGSY YTQ GdeMQe SfI SHY hKeGfjf heGFI HYO GdCda aef HOdg HYO eG SeYg aEfeG EKeg Ydi GdPjf jHOdhfg s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
Keywords: (3GdJGQjNs